2022
DOI: 10.3390/jcm11144147
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Renal Denervation in the Management of Heart Failure

Abstract: Sympathetic nervous system activation in patients with heart failure is one of the main pathophysiologic mechanisms associated with the worse outcomes. Pharmacotherapies targeting neurohormonal activation have been at the center of heart failure management. Despite the advancement of therapies and the available treatments, heart failure continues to have an overall poor prognosis. Renal denervation was originally developed to lower systemic blood pressure in patients with poorly controlled hypertension, by mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“… 31 RDN can also reduce the activation of the sympathetic nervous system throughout the whole body, as renal sympathetic afferent nerves play an important role in stimulating the activity of the hypothalamic sympathetic nervous system. 32 Moreover, studies have shown that besides its role in treating RH, RDN may also be effective in the management of other diseases associated with excessive activation of the sympathetic nervous system, such as congestive heart failure, 33 atrial fibrillation, 34 obstructive sleep apnea syndrome. 35 Therefore, the benefits of RDN may be pleiotropic, including attenuating overactivation of the sympathetic nervous system, lowering blood pressure, and improving cardiac arrhythmias, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“… 31 RDN can also reduce the activation of the sympathetic nervous system throughout the whole body, as renal sympathetic afferent nerves play an important role in stimulating the activity of the hypothalamic sympathetic nervous system. 32 Moreover, studies have shown that besides its role in treating RH, RDN may also be effective in the management of other diseases associated with excessive activation of the sympathetic nervous system, such as congestive heart failure, 33 atrial fibrillation, 34 obstructive sleep apnea syndrome. 35 Therefore, the benefits of RDN may be pleiotropic, including attenuating overactivation of the sympathetic nervous system, lowering blood pressure, and improving cardiac arrhythmias, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the tight interactions between HHF with preserved LVEF, HTN, and renal sympathetic activity, renal denervation has been promoted as a rational therapeutic approach in this patient population [104,105] (Figure 5). As the results of preliminary studies have been encouraging, renal denervation may prove useful in the management of patients with HHF and preserved LVEF, providing optimization of patient selection and improvement in ablation strategies [106].…”
Section: Nonpharmacological Neuromodulationmentioning
confidence: 99%
“…Figure 5. Neurohormonal pathways connecting the renal system to the central nervous system, cardiac, and vascular systems and the effect of renal denervation on those pathways (red arrows).permission from ref [105]…”
mentioning
confidence: 99%